2006
DOI: 10.1590/s0006-87052006000400021
|View full text |Cite
|
Sign up to set email alerts
|

Simulação do desenvolvimento da batata cultivar asterix em cinco cenários de mudanças climáticas em Santa Maria, RS

Abstract: RESUMOEm estudos do impacto de mudanças climáticas sobre agroecossistemas, um aspecto importante a quantificar é o efeito do aquecimento global sobre o desenvolvimento vegetal. O objetivo desse trabalho foi simular o impacto de cenários climáticos de aumento de temperatura do ar no desenvolvimento da batata (Solanum tuberosum L.), em Santa Maria, (RS). Cenários meteorológicos de mudanças climáticas (+2 °C, +3 °C, +4 °C, +5 °C e +6 °C) para os próximos cem anos foram gerados com Weather Generator LARS-WG usando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 31 publications
3
13
0
9
Order By: Relevance
“…A few studies, however, reported an increase in the duration of developmental phases, when temperature was increased by 2 up to 6 o C (Streck et al, 2006). These studies used different approaches to describe the effect of temperature Genotype Climate scenarios Developmental phase 1a 1b 2a 2b 3a 3b 4a 4b 5a 5b Hybrid Table 5.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A few studies, however, reported an increase in the duration of developmental phases, when temperature was increased by 2 up to 6 o C (Streck et al, 2006). These studies used different approaches to describe the effect of temperature Genotype Climate scenarios Developmental phase 1a 1b 2a 2b 3a 3b 4a 4b 5a 5b Hybrid Table 5.…”
Section: Resultsmentioning
confidence: 99%
“…One of such limitations is that most of the studies consider crops are free of insects, diseases and weeds (Lal et al, 1998;Streck et al, 2006), but some studies have demonstrated that plant pests increase in climate change scenarios (Ghini et al, 2008). These results showed that current modern rice genotypes could be less competitive with red rice in simulated future climates.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations